Localization of cis-acting sequences in the latency-related promoter of bovine herpesvirus 1 which are regulated by neuronal cell type factors and immediate-early genes. - Bratanich, A C (1992)
Bovine herpesvirus 1 (BHV-1) establishes a latent infection in sensory ganglionic neurons of cattle. During a latent infection, a single latency-related (LR) transcript is expressed. This observation suggested that DNA sequences in the LR promoter are positively regulated by neural cell type factors. The regulation of the LR gene was examined in neural cells as well as nonneural cells in transient assays. A 258-bp XbaI-SphI fragment from the LR promoter cis activated the herpes simplex virus type 1 thymidine kinase promoter in rat pheochromocytoma (PC-12) cells and differentiated human (HCN1A) neurons. In contrast, cis activation was not observed with rat (Rat-2) fibroblasts, undifferentiated HCN1A cells, or bovine turbinate cells. Treatment of PC-12 cells with nerve growth factor increased transcriptional activity of the XbaI-SphI fragment. Exonuclease III footprinting experiments suggested that nuclear factors bind to the XbaI-SphI fragment. The immediate-early genes of BHV-1 trans activated the LR promoter, and DNA sequences 5' to the XbaI-SphI fragment were necessary for maximal stimulation. These results imply that neural-cell-type-specific factors and BHV-1 immediate-early genes positively regulate LR gene expression.